Hereditary alpha-tryptasemia. Issue 5 (4th October 2022) - Bonadonna, Patrizia; Nalin, Francesca; Olivieri, Francesco
Abstract : Purpose of review: To discuss our evolving knowledge about the genetic variations in human tryptase and recent advances in associated clinical phenotypes. Recent findings: Hereditary alpha-tryptasemia (HAT) is an autosomal dominant genetic trait and a common cause of elevated basal serum tryptase (BST) in Western populations. It is a risk factor for severe anaphylaxis and an established modifier of mast cell mediator–associated symptoms among patients with systemic mastocytosis (SM). Summary: The unique properties of naturally occurring alpha/beta-tryptase heterotetramers may explain certain elements of phenotypes associated with HAT. Understanding the physiology of tryptases and how this may relate to the clinical features associated with HAT is the first step in identifying optimal medical management and targets for novel therapeutics.